2021
DOI: 10.3390/app11073050
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ecofriendly Glass Powder Concrete in Construction of Wind Farms

Abstract: Silicon is the main element in the composition of glass and it has been seen that it can be used as a partial replacement for cement in the manufacture of concrete. Different dosages of glass powder and cement were applied to manufacture the concrete mixes. Initially, the characteristics of fresh concrete were studied, such as consistency, air content, apparent density and workability. Secondly, compressive strength tests were performed on the different concrete mixtures produced. The consistency tests allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The results of the compressive strength tests of the concrete with 70% and 80% substitution of cement by glass powder are shown in Table 4. As previously observed [34], for concrete prepared with cement replaced by glass powder, the compressive strength of the concrete decreased as the amount of glass powder in the binder increased, which can be attributed to the fact that glass powder has a low pozzolanic activity at the early ages, although, in this case, the granulometry is larger and the concretes are drier and with higher air content. This causes the appearance of different C-S-H type hydrates and slower setting [31] and lower compressive strengths in the short term.…”
Section: Mechanical Properties Of Concretesupporting
confidence: 72%
See 1 more Smart Citation
“…The results of the compressive strength tests of the concrete with 70% and 80% substitution of cement by glass powder are shown in Table 4. As previously observed [34], for concrete prepared with cement replaced by glass powder, the compressive strength of the concrete decreased as the amount of glass powder in the binder increased, which can be attributed to the fact that glass powder has a low pozzolanic activity at the early ages, although, in this case, the granulometry is larger and the concretes are drier and with higher air content. This causes the appearance of different C-S-H type hydrates and slower setting [31] and lower compressive strengths in the short term.…”
Section: Mechanical Properties Of Concretesupporting
confidence: 72%
“…The percentage of glass powder substitution by cement was based on the study carried out by García del Toro et al [34], who reported that concretes manufactured with a percentage of cement substitution by glass powder higher than 50% were suitable to be used as pavements. The percentages of 70% and 80% were chosen in order to reuse a greater amount of waste and contribute in a greater extent to the circular economy and environmental protection.…”
Section: Results Of the Characterization Of Concretementioning
confidence: 99%
“…Figure 5 shows the optimal grain size curve resulting from the mixtures created. It was decided to use the theoretical Bolomey’s curve that allows one to determine the ratio between cement and water (c/w) [ 64 , 65 ]. It is possible to create a workable mixture, but surely, together with the use of fluidifying additives and indirectly with the water content of the w/c ratio, it contributes to the achievement of the required consistency class [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In turn, the data of Garcia del Toro et al indicated an increase in the degree of air entrainment of the concrete mixture with an increase in the glass content. They explained this phenomenon as the retention of the air bubbles by the surface energy of the glass being greater the finer the glass grains are [53]. However, Seong Kyum et al found a decrease in air content in concrete mixtures made with waste LCD glass [54].…”
Section: Discussionmentioning
confidence: 99%